1975
DOI: 10.1037/0022-006x.43.5.601
|View full text |Cite
|
Sign up to set email alerts
|

Importance of model similarity on extinction of avoidance behavior in children.

Abstract: This article studied the effectiveness of therapeutic modeling by using models similar or dissimilar to observers in a class of behavior being modified (fear) and a characteristic (age) seemingly irrelevant to the modeled response. Forty second-and third-grade girls who showed behavioral fear of snakes viewed models of one of four types: fearless child, fearful child, fearless adult, fearful adult. In addition, 10 subjects saw no model in a control condition. Premeasures and postmeasures of fear were taken on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
43
0
1

Year Published

1978
1978
2006
2006

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 17 publications
7
43
0
1
Order By: Relevance
“…In accord with previous work (e.g., Becker & Glidden, 1979;Berger, 1977;Hicks, 1965;Kobasigawa, 1968;Kornhaber & Schroeder, 1975;Rosekrans, 1967;Wolf, 1973), both studies show that people's responses to a stimulus become more in line with the responses of others who are similar compared with dissimilar to them. More important, both studies also showed that dissimilar others can actually induce negative opinion modeling.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In accord with previous work (e.g., Becker & Glidden, 1979;Berger, 1977;Hicks, 1965;Kobasigawa, 1968;Kornhaber & Schroeder, 1975;Rosekrans, 1967;Wolf, 1973), both studies show that people's responses to a stimulus become more in line with the responses of others who are similar compared with dissimilar to them. More important, both studies also showed that dissimilar others can actually induce negative opinion modeling.…”
Section: Discussionsupporting
confidence: 90%
“…For example, children are more likely to imitate opposite-gender role behaviors when they are performed by same-sex rather than opposite-sex models (Kobasigawa, 1968;Wolf, 1973). Also, individuals are more likely to imitate the behavior of a similar-aged model than an older or younger model when the modeled behavior is snake avoidance (Kornhaber & Schroeder, 1975), aggression (Hicks, 1965), or prosocial behavior (Becker & Glidden, 1979).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We wish to qualify the obtained benefits of observing a coping model because the subjects were children who had experienced difficulties learning mathematical skills and who had few, if any, prior successes with fractions. Therapeutic advantages of coping models typically involve fearful subjects in threatening situations fraught with failures (Kornhaber & Schroeder, 1975 ;Meichenbaum, 1971). In achievement settings, benefits of coping models might be obtained with students who find tasks anxiety provoking or who typically experience difficulties in learning new material.…”
Section: Discussionmentioning
confidence: 99%
“…The terms mastery model and coping model are derived from therapeutic contexts in which modeling is used to reduce avoidance behaviors in fearful clients (Meichenbaum, 1971 ;Thelen, Fry, Fehrenbach, & Frautschi, 1979). Coping models initially demonstrate the typical fears and deficiencies of observers but gradually improve their performance and help them gain self-confidence, whereas mastery models demonstrate faultless performance from the outset (Kazdin, 1978 ;Kornhaber & Schroeder, 1975). Coping models, which illustrate how determined effort and positive thoughts can overcome difficulties, exert beneficial effects on behavior and attitudes (Thelen et al, 1979).…”
mentioning
confidence: 99%